2020
DOI: 10.3390/pharmaceutics12030274
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinked Hyaluronan Electrospun Nanofibers for Ferulic Acid Ocular Delivery

Abstract: Electrospun nanofibers are gaining interest as ocular drug delivery platforms that may adapt to the eye surface and provide sustained release. The aim of this work was to design an innovative ophthalmic insert composed of hyaluronan (HA) nanofibers for the dual delivery of an antioxidant (ferulic acid, FA) and an antimicrobial peptide (ε-polylysine, ε-PL). Polyvinylpyrrolidone (PVP) was added to facilitate the electrospinning process. Fibers with diameters of approx. 100 nm were obtained with PVP 5%-HA 0.8% w/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…The results showed acceptable thickness of 270 ± 21 μm to 273 ± 41 μm with fiber diameter of approx. 100 nm to 1 μm; in addition, they demonstrated adequate drug release, with antimicrobial activity against Pseudomonas aeruginosa and Staphylococcus aureus [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results showed acceptable thickness of 270 ± 21 μm to 273 ± 41 μm with fiber diameter of approx. 100 nm to 1 μm; in addition, they demonstrated adequate drug release, with antimicrobial activity against Pseudomonas aeruginosa and Staphylococcus aureus [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Upon application to the ocular surface, the fibrous lens hydrates to form a film/hydrogel. A different study utilized electrospun PVP and HA nanofibers to develop hydrogels for drug delivery (185). This study focused on developing an ocular insert to deliver ferulic acid and Epsiliseen R -H for treating ocular surface conditions.…”
Section: Fibers Films Rods Extrusionsmentioning
confidence: 99%
“…Similarly, Zhang and Shen [ 50 ] demonstrated the amelioration of the hemocompatibility and reduced platelet adhesion of a potential coating film based on poly (3-hydroxybutyrate-co-3-hydroxyhexanoate) for stent application. Finally, several other studies demonstrated anti-inflammatory, anti-arrhythmic, anti-cancer activities, hepato-, and eyes-protective properties [ 51 , 52 , 53 , 54 , 55 ].…”
Section: Hydroxycinnamic Acids and Derivatives: General Uses And Current Applicationsmentioning
confidence: 99%